The Effect of Community Based Intervention on People with Type 2 Diabetes Mellitus: Systematic Review - M Agung Akbar; Junaiti Sahar; Rekawati, Etty; Ratu Ayu Dewi Sartika; Prateek Gupta (Public Health of Indonesia, 2025)
Background:The rising prevalence of Type 2 Diabetes Mellitus (T2D) has become a significant global health burden, with profound implications for healthcare systems and affected individuals. Strengthening primary healthcare services by integrating health and community-based interventions is critical for improving health outcomes. This rapid systematic review aimed to evaluate the effectiveness of community-based interventions in enhancing health outcomes for patients with T2D. Objectives:To evaluate the effectiveness of community-based interventions in managing T2D, focusing on their impact on health outcomes Methods:This systematic review adhered to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Data collection involved five major databases: Scopus, Cochrane Library, PubMed, Web of Science, and Clinical Key, covering publications from January 2013 to May 2024. Eligible studies included randomized controlled trials, mixed-methods research, clinical trials, prospective studies, experimental repeated-measures designs, and quasi-experimental designs. The risk of bias in the included studies was assessed using the RevMan 5.4.1 software. Article selection, risk of bias evaluation, data extraction, and synthesis were conducted independently by the authors, with discrepancies resolved through discussion and consensus. Results:Out of 4.463 identified articles, 13 met the eligibility criteria for inclusion in the review. The community-based intervention strategies identified in these studies involved three primary approaches: family-centered interventions, peer support, and community volunteer programs. Conclusion:This systematic review concludes that community-based interventions are effective in improving health outcomes for individuals with T2D. Integrating and strengthening health and community-based collaborations within the broader healthcare system is crucial for achieving optimal health outcomes. Nurses are encouraged to collaborate with community-based networks to bridge the gap between healthcare providers and communities, thereby enhancing public health outcomes. Keywords:community participation; diabetes mellitus; family; peer; volunteers